Newman and Manning: the Strained Relationship - Miller, Edward Jeremy (Horizons, 2008)
John Henry Cardinal Newman (1801-1890) is on the eve of being beatified. His contributions to theology and philosophy of religion are of such stature that many deem him worthy to be named a Doctor of the Church. Henry Edward Cardinal Manning (1808-1892) is thought to be the most illustrious of Westminster's archbishops since the restoration of the Catholic hierarchy in England in 1850. Newman mistrusted Manning, and Manning thought Newman lacked orthodoxy. The strained relationship began in their Anglican days and continued life long. Its story is here recounted and concludes with an explanation of why strain set in. Their very different views on the workings of authority in the Church, the role of the laity in the Church, and the Church's relationship to the world provided a sure recipe for their continued alienation.